Analisis Pemenuhan Persyaratan Food Savety System Certification 22000 di Industri Kemasan Pangan - Jamal Zamrudi; Harsi Dewantari Kusumaningrum; Lilis Nuraida (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
Food Safety System Certification 22000 (FSSC 22000) as food safety management system recently becomes requisition required by customers, consisting of ISO 22000, PAS 223:2011, and additional requirements. The purpose of this study was to develop recommendations and establish a simple strategy model in compliance with FSSC 22000 requirements. The methods used were identifying food safety regulations related to FSSC 22000, assessing the actual condition of PT XYZ as a case study, developing recommendations on the found gaps, and developing a simple strategy model. PT XYZ has ful lled 63% of the requirements, with in detail compliance of ISO 22000, PAS 223: 2011, and their additional requirements were 55%, 70%, and 20% respectively. Food safety management system has not been well socialized that caused lacking of personnel awareness, infrastructure and documentation implemention, and food safety requirement for supplier selection. The strategy to meet the food safety system requirement incudes action, plan, training, infrastructure improvement, documentation review, food safety training for suppliers, internal audit, and external audit. It was concluded that the strategy model developed has been effective in helping the company to meet the FSSC 22000 requirements.